Efeito potencializador da Angiotensina(1-7) sobre o aumento da tensão sistólica induzida pelo isoproterenol em corações isolados de ratos - Amilton Cerqueira de Andrade (2011)
The present study was designed to establish the possible interaction between the Angiotensin-(1-7) [Ang-(1-7)] with isoproterenol, adrenergic agonist, in the production of increased myocardial contractility of isolated hearts of adult rats. Hearts were perfused according to Langendorff preparation. It was used first bolus of isoproterenol, laterally to the aortic clamp. After a stabilization period, it was then applied a infusion of a Angiotensin(1-7) solution, for 10 minutes, and than another bolus of Isoproterenol. The values of contraction force and heart rate were registered, each 15 seconds, in six samples. It was used the Biopac®System sofftware. As reported by many studies of other authors, the Ang-(1-7) alone does not produce important modification in force or heart rate values. But it was found proportional increase of contractil force induced by isoproterenol after Ang(1-7) application. To compare adrenergic action, it was used pre-treatment with atenolol ( blocker), with prevention of the increased contraction force implemented by Isoproterenol. It was used A-779, a Ang-(1-7) antagonist. It prevented the isoproterenol action after Ang-(1-7). There was a discret increase in cardiac heart rate after isoproterenol treatment, but no significative difference was found with Ang(1-7) and Isoproterenol combination. These data suggest that Ang-(1-7) exerts a potentialization over the isoproterenol action by increasing the myocardial contraction force and, maybe, a interaction between receptors and receptor Mas, the specific receptor for Angiotensin(1-7).